THE INFLUENCE OF BRAND IMAGE AND TASTE ON PRICE PERCEPTION AND ITS IMPLICATIONS ON CUSTOMER LOYALTY AT INDIA RESTAURANT, TEBING TINGGI - Alfina Yusra; Hanna Sajidah Sinaga; Sarwoto; Imelda Mardayanti (RADJA PUBLIKA, 2025)
This study aims to analyze the effect of Brand Image (X1) and Taste (X2) on Customer Loyalty (Y), both directly and through Price Perception (Z) as a mediating variable, on Indian restaurant customers. This study was conducted for 2 months starting from February-April 2025. The method used in this study is a quantitative approach with path analysis techniques. Primary data were collected by distributing questionnaires to Indian Restaurant customers, with a total of 80 respondents, which were obtained using the Slovin formula with a margin of error of 5%. Data collection using a questionnaire using a google form. Based on the results of the calculation using bootstapping, the R2 value of the price perception variable is 0.518, which means that price perception is influenced by brand image and taste by 51.8% or in other words, the contribution of brand image and taste is 51.8% while the remaining 48.2% is the contribution of other variables not discussed in this study such as price references, product quality, brand trust and others. then it is known that the R2 value of the customer loyalty variable is 0.174 which means that customer loyalty is influenced by brand image and taste by 17.4% or in other words the contribution of brand image and taste is 17.4% while the remaining 82.6% is the contribution of other variables.